BENTUK PARTISIPASI MASYARAKAT DALAM MENDIRIKAN MADRASAH IBTIDAIYAH AR-RAHMAN DI DESA WIDODAREN KECAMATAN WIDODAREN KABUPATEN NGAWI - Nur Hidayah; Abdur Rahim (Bajang Institute, 2022)
Abstract: That in the context of developing national education, the active participation of the entire community is required. The forms of participation that have developed so far are very varied, depending on the situation and conditions of each region. In addition to the participation of the entire community, it is absolutely necessary for government policies to always support the direction of increasing the number and quality of educational institutions at all levels, including Islamic religious education. This study aims to determine the form of community participation and government policies in establishing/developing Madrasah Ibtidaiyah Ar-Rahman in Widodaren Village, Widodaren District, Ngawi Regency. The subjects of the research were the staff of the Ministry of Religion of Ngawi Regency, the Chairperson of the Ar-Rahman Widodaren Foundation, the Head of the Ibtidaiyah Madrasah Ar-Rahman Widodaren, a number of parents of students and members of the community around MI Ar-Rahman Widodaren. This type of research is descriptive qualitative with data collection techniques: interviews, observation, and documentation. Data analysis using a single site; and checking the validity of the data using triangulation techniques and confirmability criteria. The results of the study show that: (1) the form of community participation in the development of MI Ar-Rahman Widodaren, in physical form including waqf land from residents, money, materials, teak wood, building power, consumption, benches, and shuttle car facilities, and school library books. Non-physical forms of community participation include ideas or contributions from community leaders, religious leaders, and other non-formal figures; and (2) government policies in the development of MI Ar-Rahman Widodaren in the form of administrative and non-administrative assistance, including planning, implementing, and evaluating the development program of MI Ar-Rahman Widodaren, including funding for School Operational Fees (BOS) and state teachers. which is still ongoing today.